EFFECTIVENESS OF TILLAGE SYSTEMS AND FARM MANURE LEVELS ON RICE PRODUCTIVITY - S. Nazeer; A. U. Malik; G. Nazir; J. Ahmad (Journal of Animal and Plant Sciences, 2012)
Tillage management practices and farm manure application are among the most important factors affecting paddy yield. A field experiment was conducted at research area of University of Agriculture, Faisalabad, Pakistan for the purpose to investigate the effect of two tillage systems (Conventional tillage-CT ; Deep tillage-DT) under three farm manure application levels (No farm manure, 20 and 40 Mg ha-1) on yield and yield components of rice crop. The experiment was carried out in randomized complete block design with split plot arrangements with three replications. All necessary parameters were observed through standard procedures. The results revealed that both tillage systems and farm manure application levels significantly affected yield and most of the yield contributing components in rice under local conditions. Among tillage methods, the maximum values of paddy yield (2911 Kg ha-1) were observed in the case of deep tillage. The effect of tillage and FM significantly affected growth of rice as it increased the plant height, paddy yield, and 1000 grain weight. Maximum value of plant height (97.50 cm), number of tillers (11.80), number of grains per tiller (116), paddy yield (3003 Kg ha-1), 1000 grains weight (23.00 g), were observed in case of FM application level of 40 Mg ha-1. The interactive effect of tillage systems and farm manure application levels also resulted better for most of the yield contributing parameters and paddy yield (3925 Kg ha-1). It is concluded that tillage methods and farm manure use are imperative for rice crop productivity and there come out substantial differences on rice yield.
Keywords: Tillage systems; Farm manure levels; paddy yield; rice; Pakistan.